CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE TENTH GRADE - Yuliastuti Yuliastuti; Sriati Usman (Tadulako University, 2021)
The purpose of this research is to find out the correlation between vocabulary mastery and reading comprehension of the tenth Grade students of SMAN 14 Sigi. This research used quantitative with correlational approach. The sample was 42 students which was taken by using all population sampling/all sampling technique. The instruments used to collect the data were the vocabulary and reading comprehension test in multiple choices form. All the data gained in this research were analyzed using Pearson Product Moment Formula. The result shows that the obtained r value is 0.703. it is categorized in “Substantial” correlation. It indicated that there is positive correlation between vocabulary mastery and reading comprehension of the tenth grade students of SMAN 14 Sigi. Vocabulary contributes significantly to their reading comprehension. When they mastered the vocabulary, it will be easier for them to comprehend the reading. In the other words, vocabulary affect the reading comprehension and vice versa.